2008
DOI: 10.1029/2008gl035338
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Titan's low altitude ionized layer from the Relaxation Probe onboard HUYGENS

Abstract: [1] Some of the secrets of the atmosphere of Titan have been unveiled by the Huygens Probe. The Permitivity Wave and Altimetry system detected a hidden ionosphere much below the main ionosphere, that lies between 600 and 2000 km. Theoretical models predicted a low altitude ionosphere produced by cosmic rays that, contrary to magnetospheric particles and UV photons, are able to penetrate down in the atmosphere. Two sensors: Mutual Impedance (MI) and Relaxation Probe (RP) measured the conductivity of the ionosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(51 citation statements)
references
References 24 publications
4
46
1
Order By: Relevance
“…These authors concluded that in order to explain the observed disk emissions, the scattered stellar light from Titan's disk is the most likely scenario. It is worth mentioning, however, that according to Gronoff et al (2011), the ionization by each Z-group of cosmic rays in the atmosphere of Titan results in the formation of an ionization layer peaking at 65 km altitude, independently of the solar activity, in consistency with the Huygens measurements (Hamelin et al 2007;López-Moreno et al 2008). The observed correlation between cosmic ray ionization altitudes and aerosol layers urges for further investigations in this direction in the future.…”
Section: The Role Of Galactic Cosmic Rays and Transient Eventsmentioning
confidence: 81%
See 1 more Smart Citation
“…These authors concluded that in order to explain the observed disk emissions, the scattered stellar light from Titan's disk is the most likely scenario. It is worth mentioning, however, that according to Gronoff et al (2011), the ionization by each Z-group of cosmic rays in the atmosphere of Titan results in the formation of an ionization layer peaking at 65 km altitude, independently of the solar activity, in consistency with the Huygens measurements (Hamelin et al 2007;López-Moreno et al 2008). The observed correlation between cosmic ray ionization altitudes and aerosol layers urges for further investigations in this direction in the future.…”
Section: The Role Of Galactic Cosmic Rays and Transient Eventsmentioning
confidence: 81%
“…Each source has a main ionization altitude that creates several ionospheric layers above 50 km (Hamelin et al 2007;Cravens et al 2008Cravens et al , 2009López-Moreno et al 2008, and references therein). The ion production rates in Titan's ionosphere, for the dayside (Richard et al 2015a and references therein) and nightside (Richard et al 2015b and references therein), have been extensively studied.…”
Section: Space Weather At the Saturnian Moonsmentioning
confidence: 99%
“…Imanaka et al, 2004;Lavvas et al, 2011b). PAH emissions in Titan's upper atmosphere have already been suggested in order to explain an unidentified emission feature close to 3.3 lm (López-Puertas et al, 2013). Individual PAHs can also emit at visible wavelengths when excited, while laboratory experiments on tholins have shown that indeed these Titan aerosol analogs fluoresce at wavelengths between 400 and 600 nm depending on the experimental conditions (Hodyss et al, 2004).…”
Section: Discussionmentioning
confidence: 96%
“…Direct observations of the cosmic ray input in Titan's atmosphere are not available and we only know their influence indirectly: cosmic rays are the only means of ionization of the main gaseous compounds (N 2 , CH 4 ) in the lower atmosphere, since solar photons with the appropriate energies are absorbed much higher in the atmosphere; therefore, the local ionosphere observed in Titan's lower atmosphere by the Huygens probe (López-Moreno et al, 2008) is a clear indication of cosmic ray deposition. This energy input is also temporally variable since the flow of energetic particles in the Solar System is affected by the solar wind strength.…”
Section: Energy Depositionmentioning
confidence: 99%
“…2, Ågren et al 2009). Other prominent ionospheric peaks have been identified at 500-600 km altitude (Kliore et al 2008;Cravens et al 2008aCravens et al , 2008b and at 60-80 km altitude (López-Moreno et al 2008), and mainly reflect the different ionization sources acting on Titan's atmosphere at different altitudes (see below). The ionization levels remain high (100-1000 cm −3 ) throughout the atmosphere where measurements have been made.…”
Section: Titan's Ionospheric Structurementioning
confidence: 98%